Immobilization of Dystrophin and Laminin α2-Chain Deficient Zebrafish Larvae In Vivo Prevents the Development of Muscular Dystrophy. - Mei Li; Anders Arner (PLoS ONE, 2015)
Muscular dystrophies are often caused by genetic alterations in the dystrophin-dystroglycan complex or its extracellular ligands. These structures are associated with the cell membrane and provide mechanical links between the cytoskeleton and the matrix. Mechanical stress is considered a pathological mechanism and muscle immobilization has been shown to be beneficial in some mouse models of muscular dystrophy. The zebrafish enables novel and less complex models to examine the effects of extended immobilization or muscle relaxation in vivo in different dystrophy models. We have examined effects of immobilization in larvae from two zebrafish strains with muscular dystrophy, the Sapje dystrophin-deficient and the Candyfloss laminin α2-chain-deficient strains. Larvae (4 days post fertilization, dpf) of both mutants have significantly lower active force in vitro, alterations in the muscle structure with gaps between muscle fibers and altered birefringence patterns compared to their normal siblings. Complete immobilization (18 hrs to 4 dpf) was achieved using a small molecular inhibitor of actin-myosin interaction (BTS, 50 μM). This treatment resulted in a significantly weaker active contraction at 4 dpf in both mutated larvae and normal siblings, most likely reflecting a general effect of immobilization on myofibrillogenesis. The immobilization also significantly reduced the structural damage in the mutated strains, showing that muscle activity is an important pathological mechanism. Following one-day washout of BTS, muscle tension partly recovered in the Candyfloss siblings and caused structural damage in these mutants, indicating activity-induced muscle recovery and damage, respectively.